HUBUNGAN SELF CONFIDENCE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA - Nurojab, Evi Supriatna; Sari, Veny Triyana Andika (IKIP Siliwangi, 2019)
This research to find out in depth about the relationship of self confidence to the ability to problem solving mathematics SMK students. The population in this research is SMK in Cipatat. Instrument in this research in the form of description of ability of mathematics problem solving as much as 5 item, and self confidence questionnaire of student as much 30 statement. Methods in this research using correlational research methods. The result of this research shows that there is a correlation (r) value on Person Corellation between self confidence with students’ mathematics problem solving ability is 0,597**. Form these results show the level of relationships that are classified and indicate the direction of a positive relationship